ILLUSTRATION OF INTANGIBLE CULTURAL HERITAGE OF SEMARANG CITY - Putranto, Bagas Dwi (Eduarts: Jurnal Pendidikan Seni, 2026)
The cultural diversity of Indonesia is also reflected in the intangible cultural heritage (ICH) that lives and thrives within local communities. In Semarang City, various traditional customs, culinary arts, and performing arts represent cultural expressions passed down across generations. However, in the digital era, many younger audiences are less familiar with these traditions. This artistic project explores Semarang's ICH through digital illustration in the line art style, adapted from vintage postage stamps. The project aims to educate and reintroduce cultural identity visually using digital technology as a creative medium. The result is a series of artworks combining narrative, culture, and artistic expression in a communicative and aesthetic way.